Experimental modal analysis of vehicle exhaust system to determine hanger location using root mean square value - Oo, Kyaw Nyein (2015)
Vibration of exhaust system due to the engine operation and the condition of the road surface which is transferable to the body through the hanger affects the noise, vibration and harshness performance of the vehicle, and the life time of the hangers. In order to solve this problem of the automobile exhaust system, experimental modal analysis was carried out by utilizing a sample exhaust system of passenger car as a research object within the frequency of interest. LMS Test. Lab was used to perform modal analysis. This study estimated the dynamic characteristics of the exhaust system such as natural frequencies and mode shapes. Using frequency response function at every measuring point, root mean square value (RMS) of vibrating energy was calculated to select hanger location of exhaust system where the RMS value is comparatively small. Experimental modal analysis is an efficient tool to study and estimate the dynamic properties of the exhaust system, and calculating RMS value is also an easy method to find hanger location of the exhaust system utilizing frequency response function.